Performance of briquettes produced from sawdust of gmelina arborea and montmorillonite clay as binder (2023)
Clay had been used as binders in briquetting research activities, however their performance characterization in terms of quality and combustion have not been clearly evaluated or reported. This study therefore provide a qualitative evaluation of briquettes produced using sawdust of Gmelina arborea and montmorillonite clay. Sun-dried sawdust (~9% moisture contents) obtained from sawmills in Ishiagu, Ebonyi State were mixed with processed clay samples collected from earthen pot mould sites characterized, then used in briquette production using five mixing ratios of 90:10, 80:20, 70:30, 60:40, & 50:50 (weight/weight)% and standard test procedures for characterization. Data were analyzed using SPSS at p< 0.05 significance levels. The quality characteristics of clay briquettes compared favourably with other binder types with an increase in performance as binder concentration increases. The briquettes combustion performance in air and stove are significantly affected by the agglomerated non-combustible clay particle impregnating the biomass matrix. Best combustion performance occurred at 10% binder concentration with no significant value-addition to ignition time, flame combustion and heating values. Above 10% binder addition, briquettes failed self-ignition, flame combustion, and retarded char combustion tests. This implied clay is a poor performing binder and the associated briquette are combustibly poor.